Remedy vs. Diagnosis. How Political Liberalism Accounts for Political Disagreement (in Polish) (Diametros, 2013)
The problem of political disagreement is one of the most important problems, which provides the starting point for the construction of any contemporary political theory. Moreover, each and every theory can be evaluated by taking into account the efficacy of coping with different types of political disagreements. This paper discusses four different types of political disagreement (the error theory, value pluralism, the essential contestability of concepts, Lakoff’s metaphor theory) and aims at answering the question whether the theory of political liberalism (founded by J. Rawls) is a good (i.e. efficacious) remedy for political disagreement. The result is moderately positive, as far as it reveals the weak points of this theory.
Keywords: J. Rawls; W. B. Gallie; G. Lakoff; disagreement; error theory; essentially contested concepts